Passive exposure to heat improves glucose metabolism in overweight humans. (1st June 2020) - Pallubinsky, Hannah; Phielix, Esther; Dautzenberg, Bas; Schaart, Gert; Connell, Niels J.; de Wit‐Verheggen, Vera; Havekes, Bas; van Baak, Marleen A.; Schrauwen, Patrick; van Marken Lichtenbelt, Wouter D.
Abstract: Aim: Heat exposure has been indicated to positively affect glucose metabolism. An involvement of heat shock protein 72 (HSP72) in the enhancement of insulin sensitivity upon heat exposure has been previously suggested. Here, we performed an intervention study exploring the effect of passive heat acclimation (PHA) on glucose metabolism and intracellular (a) HSP72 concentrations in overweight humans. Methods: Eleven non‐diabetic overweight (BMI 27‐35 kg/m 2 ) participants underwent 10 consecutive days of PHA (4‐6 h/day, 34.4 ± 0.2°C, 22.8 ± 2.7%RH). Before and after PHA, whole‐body insulin sensitivity was assessed using a one‐step hyperinsulinaemic‐euglycaemic clamp, skeletal muscle biopsies were taken to measure intracellular iHSP72, energy expenditure and substrate oxidation were measured using indirect calorimetry and blood samples were drawn to assess markers of metabolic health. Thermophysiological adaptations were measured during a temperature ramp protocol before and after PHA. Results: Despite a lack of change in iHSP72, 10 days of PHA reduced basal (9.7 ± 1.4 pre‐ vs 8.4 ± 2.1 μmol · kg –1 · min –1 post‐PHA, P = .038) and insulin‐stimulated (2.1 ± 0.9 pre‐ vs 1.5 ± 0.8 μmol · kg –1 · min –1 post‐PHA, P = .005) endogenous glucose production (EGP) and increased insulin suppression of EGP (78.5 ± 9.7% pre‐ vs 83.0 ± 7.9% post‐PHA, P = .028). Consistently, fasting plasma glucose (6.0 ± 0.5 pre‐ vs 5.8 ± 0.4 mmol/L post‐PHA, P = .013) and insulin concentrations (97 ± 55 pre‐ vs 84 ± 49 pmol/L post‐PHA, P = .026) decreased significantly. Moreover, fat oxidation increased, and free fatty acids as well as cholesterol concentrations and mean arterial pressure decreased after PHA. Conclusion: Our results show that PHA for 10 days improves glucose metabolism and enhances fat metabolism, without changes in iHSP72. Further exploration of the therapeutic role of heat in cardio‐metabolic disorders should be considered.